PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN DENGAN UKURAN PERUSAHAAN SEBAGAI MODERATOR (Studi Empiris Pada Perusahaan Non Keuangan yang Terdaftar di Bursa Efek Indonesia Pada Tahun 2015 - 2019) - Junenti Silalahi; Saur Melianna; Winarto Winarto; Gracesiela Yosephine Simanjuntak (Sekolah Tinggi Ilmu Ekonomi-LMII Medan, 2022)
This study aims to determine the independent variables (independent) namely the Board of Commissioners, the Audit Committee, and the Board of Directors on the value of the company with the size of the company as a moderating variable. This research was conducted on non-financial companies listed on the Indonesia Stock Exchange (IDX) in 2015-2019. Sample selection was done by purposive sampling method from 609 and obtained 9 samples that met the requirements. The data analysis method used in this study is descriptive statistical analysis method, classical assumption test (normality test, multicollinearity test, autocorrelation test, heteroscedasticity test), moderating regression analysis, and hypothesis testing (hypothesis testing). partially (F test), hypothesis testing simultaneously (t test), and coefficient of determination test (R2). The results of this study indicate that: 1) The Board of Commissioners and Board of Directors have no effect but significant on firm value, the Audit Committee has an effect and significant to Company Value. 2) Company size as a moderating variable is able to moderate the relationship between the Board of Directors and Company Value.